OP46 Sedentary behaviour of adolescents in Glasgow compared with the rest of Scotland: the mediating effect of the neighbourhood context. (2nd September 2014) - Levin, KA; Walsh, D; McCartney, G
Abstract : Background: Studies of adult health have shown poor outcomes for Glasgow compared with the rest of Scotland (RoS). Sedentary behaviour in adolescence is associated with unhealthy snacking, obesity and sleeping difficulties. The aim of this study is to describe sedentary behaviour in Glasgow relative to RoS, and to assess whether sense of belonging, local environment and greenspace use mediate this relationship. Methods: Data from the 2010 Scottish Health Behaviour in School-Aged Children survey were modelled using multilevel linear modelling for outcomes: TV watching (TVW), computer use (CU) and computer game play (CGP) (hours per day), adjusting for age, sex, family structure, family socioeconomic status (SES), school type and rurality Results: Young people's TVW, CU and CGP was significantly greater in Glasgow than in RoS; respectively, mean = 2.93, 2.38, 2.96 hrs per day in Glasgow, compared with mean = 2.61, 2.04, 2.45 hrs in the RoS. There were clear differences in SES geographically, with only 55% of young people from Glasgow categorised as coming from a family with high SES, compared with 70% living in RoS. Young people had a lower sense of belonging in Glasgow and a poorer perception of their local environment. They also used local greenspace on fewer days per week. Modelling the data and adjusting for demographic factors, showed that young Glaswegians watched TV 0.42 (SE= 0.13) hours more per day. After adjustment for SES and family structure, this reduced to 0.40 (0.12) and after adjustment for local environment became 0.35 (0.12). Under the Sobel test, partial mediation was significant (p = 0.008). Similarly, Glasgow's CU was on average 0.51 (0.15) greater than RoS, reducing to 0.46 (0.15) after adjustment for SES, and 0.40 (0.14) after adjustment for sense of belonging, perception of local environment and greenspace use. All but greenspace use were found to be significant mediators of the relationship between sedentary behaviour and Glasgow residence. Greenspace use was in fact positively related to CU. CGP was also greater in Glasgow; Beta = 0.42 (0.15) after adjustment for SES, reducing to 0.37 (0.15) on adjustment for sense of belonging capital (p = 0.014 under the Sobel test). Conclusion: Sedentary behaviour is higher in Glasgow compared with RoS for TV and computer use outcomes. Sense of belonging and perception of local environment partially mediate the relationship between sedentary behaviour and Glasgow residence, explaining albeit only a small proportion (approximately 12%) of the difference. Policy makers should consider the neighbourhood context when addressing adolescent sedentary behaviour.